Gathering Pace / Continental Europe 1870-1945 - Larkin Maurice (Humanities Press, 1970)
This book is about the people of Europe between 1870 and 1945. Acknowledgements, Gathering Pace - and Growing Uniformity, 1870 to 1918, The Common Factors, Eastern Empires, The South-West, From Sedan to Sarajevo, Disaster, 1918 to 1945, Paying the Cost, The Great Experiment, Humiliation and Its Price, Democracy Surviving, The Collapse of Democracy, Good Intentions and the Road to Ruin, Vision of Uniformity, Brief Lives, Bibliography, Index.